Morphological characterization of Bitter gourd (Momordica charantia L.) Genotypes and their Hybrids - Shyam Prakash; C.N. Ram; Anil Kumar; Aastik Jha; Suman Poonia; Virendra Kumar; Akhil Kumar Chaudhary; Pravesh Kumar (The Bioscan, 2025)
The present investigation was carried out for successive two years during summer season of 2022-23 and 2024-25 to carry out characterization of 44 genotypes (30 F1 + 13 parents) including 1 check of bitter gourd (Momordica charantia L.) at Main Experimental Research Station, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, Uttar Pradesh India.